RESPON PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) DENGAN APLIKASI KOMBINASI PUPUK DAN JARAK TANAM - Mariyatul Qibtiyah; Charir Hasan Mahmudi; Istiqomah Istiqomah (AGRORADIX : Jurnal Ilmu Pertanian, 2021)
Peanut production in Indonesia is not optimal due to inadequate cultivation techniques, this has an impact on increasing domestic demand but is not fulfilled, so it must be international trade. To overcome this, it can be done by applying a combination of organic and inorganic fertilizers, as well as fostering spacing for growth growth and yield of peanut plants. This research was conducted in Tegal Rejo village, Mbrao hamlet, Widang sub-district, Tuban regency, East Java. The research was conducted in February-April 2021. This research_used factorial randomized_block design with 2_treatment factors and 3 replications, the first factor was a combination of compound fertilizers and the second was spacing. Observations were carried out from the age of 14 days after planting and then continued once in 7 days.